Impact of an environmentally realistic intake of water contaminants and superoxide formation on tissues of rats - Silva, AMM; Novelli, ELB; Fascineli, M. L.; Almeida, J. A. (Elsevier B.V., 1999)
Water contaminants have a high potential risk for the health of populations and for this reason their toxic effects urgently should be established. The present study was carried out to determine whether an environmentally realistic intake of water contaminants can induce tissue lesions, and to clarify the contribution of superoxide radical (O-2(.-)) formation to this effect. Male Wistar rats were given drinking water from the Tiett River (group A) and from the Capivara River (group B). The increased creatinine, glucose, alanine transaminase and amylase levels in serum reflected the toxic effects of river-water contaminants to renal, pancreatic and hepatic tissues of rats. As changes in lipoperoxide were observed in rats after river-water intake while superoxide dismutase activities decreased in these animals, it is assumed that the superoxide anion elicits lipoperoxide formation and induces tissue damage. There is evidence that oxygen tension reflects water pollution, since river-water with a-low oxygen tension induced more elevated toxicity in rat tissues. (C) 1999 Elsevier B.V. Ltd. All rights reserved.
Keywords: river-water; contaminants; toxicity; superoxide; rats